O potrzebie ekspresji muzyczno-ruchowej w szkole podstawowej = The need for musical expression and movement in primary school - Jatczak, Anita (Zielona Góra ; Skarbona: Stowarzyszenie Polskich Muzyków Kameralistów)
The article describes the influence of musical plays on the memory, concentration and abstract thinking. What`s more it also impact on developing musical talents throug the attendance in musical and kinestetic classes or courses. This article focuses also on the musical plays which have got a positive impact on the educational issne/aspects, Moreover, the author presents its influence on the whole organizm`s development.
Keywords: zajęcia muzyczno-ruchowe; zabawy muzyczne; nauczyciele; uczeń; koncentracja; pamięć; myślenie abstrakcyjne; class music and movement activities; music; teacher; pupil; concentration; memory; abstract thinking